Abundance and distribution of the white shark in the Mediterranean Sea. Issue 2 (27th December 2019) - Moro, Stefano; Jona‐Lasinio, Giovanna; Block, Barbara; Micheli, Fiorenza; De Leo, Giulio; Serena, Fabrizio; Bottaro, Massimiliano; Scacco, Umberto; Ferretti, Francesco
Abstract: Conservation of apex predators is a key challenge both in marine and terrestrial ecosystems. The white shark is a rare but persistent inhabitant of the Mediterranean Sea and it is currently assessed as "critically endangered" in the region. However, the population trends and dynamics of this species in the area are still unknown. Little is known about white shark distribution, habitat use and population abundance trends, aspects that are critical for conservation and management. In this study, we built the most comprehensive database of white shark occurrence records in the region. We collected 773 different records from different sources and used them to characterize the spatial and temporal patterns of abundance of Mediterranean white sharks between 1860 and 2016. We analysed these data by using generalized additive models and used spatially disaggregated information on human population abundance as a proxy of observation effort. Our results suggest a complex trajectory of population change characterized by a historical increase and a more recent reduction (61%, range 58%–72%) since the second half of the 20th century. In particular, analyses reveal a 52% (range 37%–88%) to 96% (range 92%–100%) overall decline in different Mediterranean sectors and a contraction in spatial distribution. Here, we provide the first reconstruction of abundance trends and offer new hypotheses regarding the drivers of change of white sharks in the Mediterranean. Our approach can be broadly applied to data‐poor contexts to reconstruct change and inform the conservation of endangered top predators in the Mediterranean Sea and other intensely used marine regions.